The Nuṣayrī-ʿAlawīs: an introduction to the religion, history, and identity of the leading minority in Syria - Friedman, Yaron (Islamic history and civilization 0929-2403, 2010)
A century after Dussaud's "Histoire et religion des NosairA(R)s" (1900), new light is shed on the medieval history and the mysterious religion of the leading sect in Syria in a comprehensive and updated study of the NuaayrA-a ~AlawAs